Enhancing nutrient uptake and grapefruit (Citrus paradisi) growth through soil application of beneficial bacteria (Bacillus spp.) - Cano-Castro, Laura; Li, Jinyun; Wang, Nian; Strauss, Sarah L.; Schumann, Arnold W. (Frontiers in Horticulture, 2024)
The increasing demand for sustainable food production necessitates a shift towards agricultural practices that mitigate adverse environmental impact. Excessive use of chemical fertilizers and pesticides has raised concerns, prompting a surge of interest in harnessing the potential of beneficial soil microorganisms, particularly plant growth-promoting rhizobacteria (PGPR). This study explores the impact of PGPR treatments on grapefruit seedlings, including a commercial strain of Bacillus velezensis, a fresh inoculum of Bacillus amyloliquefaciens, a mixture of three selected citrus endophytic Bacillus spp. isolates, inorganic fertilizers, and combinations thereof. Results indicated that the combination of Bacillus velezensis and inorganic fertilization significantly improved soil nutrient availability and enhanced plant growth, surpassing both negative (water) and positive (inorganic fertilization) controls. Shoot and root system biomass showed significant increases from Bacillus velezensis plus inorganic fertilization compared to other treatments. These findings provide insights into management methods that can reduce chemical inputs while promoting plant productivity. The demonstrated benefits of PGPR on grapefruit seedlings highlights a promising approach for future research and applications in sustainable citrus cultivation.